2020
DOI: 10.35848/1347-4065/abb250
|View full text |Cite
|
Sign up to set email alerts
|

Threshold voltage shift-proof circular oxide thin film transistor with top and bottom gates for high bending stability

Abstract: Negligible threshold-voltage shift is reported for oxide thin-film transistors (TFTs) under high current (3 μA) and tensile bending stress (2 mm radius). The good stability is attributed to a circular TFT structure with electrically shorted top and bottom gates, and a polyimide substrate embedded with carbon-nanotubes for mechanical support and damage-free detachment from carrier glass. The circular structure leads to uniform electric field distribution across the channel, hard saturation in output characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
0
1
0
Order By: Relevance
“…Although the subthreshold swing, turn-on voltage, uniformity, and hysteresis values were excellent, the output characteristics showed that the drain current was not saturated at a high drain voltage. As the current saturation characteristics of TFTs have important effects on driving the μLEDs with constant luminance, 48 the driving TFTs must have a saturation drain current at a specific drain voltage. In addition, the turn-on-voltage shift was −7.07 V during the NBIS stability measurements over 10 000 s at −1 MV cm −1 and 0.5 mW cm −2 white light stress.…”
Section: Resultsmentioning
confidence: 99%
“…Although the subthreshold swing, turn-on voltage, uniformity, and hysteresis values were excellent, the output characteristics showed that the drain current was not saturated at a high drain voltage. As the current saturation characteristics of TFTs have important effects on driving the μLEDs with constant luminance, 48 the driving TFTs must have a saturation drain current at a specific drain voltage. In addition, the turn-on-voltage shift was −7.07 V during the NBIS stability measurements over 10 000 s at −1 MV cm −1 and 0.5 mW cm −2 white light stress.…”
Section: Resultsmentioning
confidence: 99%
“…While the influence of bending on the dc and ac performance of flexible IGZO TFTs has been investigated in the past [27], the flexibility of double-gate TFTs was explored in the dc domain [12], [18], [28], or for TFTs with connected top and bottom gates [19]. Therefore, it is important to ensure that the described tunable devices stay functional when exposed to mechanical strain.…”
Section: Flexibilitymentioning
confidence: 99%
“…Nevertheless, the use of multigate structures has also been proven to be useful in improving the performance of flexible oxide-based devices and circuits. Additional gates in TFTs can modulate the threshold voltage [11], [12], enable unipolar circuits with CMOS-like operation principles [13], improve the electrical stability of transistors [14], reduce mechanical strain [15], be used for sensing applications [16], influence the noise performance [17], and also increase their ON/OFF ratio and effective mobility [18]. However, the ac performance of such devices has not been sufficiently investigated.…”
Section: Introductionmentioning
confidence: 99%